Problematika Kebijakan Pembelajaran Bauran di Masa Pandemi Covid-19 dalam Memenuhi Hak atas Pendidikan: The Problems of Mixed Learning Policy in the Covid-19 Pandemic Period in Fulfilling the Right to Education - Handyanto, Shahyb; Hidayat, Arifin (Fakultas Hukum Universitas Negeri Semarang, 2021)
The Covid-19 pandemic that hit Indonesia and the world had a significant impact on education. The government has taken a policy by conducting distance learning. However, distance learning creates its problems and in the end, it has violated the constitutional rights of students and has proven ineffective in the transfer of knowledge process. Thus the goal of educating the nation's life becomes constrained. This study aims to examine whether a learning policy that is carried out in a mixed manner (a combination of online and offline) will make the learning process more effective or will it have a negative effect, mainly related to the potential for Covid-19 transmission. The formulation of the problem in this study are: first, how are education policy during the Covid-19 pandemic and the impact of Covid-19 on education in Indonesia. Second, how the learning mix policy can make learning effective or create new problems.